Struktur Anatomi dan Kualitas Serat Kayu dan Akar Gantung Beringin (Ficus benjamina Linn.) - . Krisdianto; Jamal Balfas (Jurnal Ilmu Pertanian Indonesia, 2016)
Beringin (Ficus benjamina Linn.) is one of typical fast growing tree species which are commonly found in Indonesia. The trees grow with hanging roots which grow larger and often can merged with the main stem, then its timber is not optimally utilized. This paper studies the anatomical structure and fiber quality of main stem and large, medium, and small diameter of hanging roots of beringin (Ficus benjamina Linn.) tree. Anatomical structure was observed macroscopically and microscopically, while fiber dimensions were measured from macerated samples. The results show that the anatomical structure pattern of the roots is similar with those of main stem, however the quantity and dimension of anatomical components of hanging roots are smaller and shorter than components of main stem. Likewise, the fiber dimensions of roots are shorter and thinner than those taken from the main stem. Based on fiber dimensions and its derivative value, beringin wood fibers are classified into class quality II for pulp and paper. The creamy white color with white streaky figure of beringin wood from main stem is recommended for indoor decoration products such as wooden venetian blind, while the small roots are recommended for strap or webbing material crafts.